Production of phytolith and PhytOC and distribution of extractable Si Pools in aerobic rice as influenced by different Si sources - Anjum, Mohsina; Prakash, Nagabovanalli Basavarajappa (Frontiers in Plant Science, 2023)
Phytoliths are composed of 66 to 91% SiO2 and 1 to 6% organic carbon (C) known as phytolith occluded carbon (phytOCPhytOC). PhytOC is critical for long-term C storage in the agroecosystem. A field experiment was carried out to investigate the effect of three different sources of exogenous Si, i.e., diatomaceous earth (DE), silicic acid (SA) and rice husk biochar (RHB) on 1) plant phytolith, C content in phytolith and PhytOC content in different rice organs;2) relationship between plant phytolith, C content in phytolith, PhytOC content, and soil properties (; and 3) soil physicochemical properties and readily soluble silicon pools). Different Si sources produced significantly higher phytolith, PhytOC content, and readily soluble Si pools (CCSi, AASi, and ASi) than the control (RDF), with treatment receiving RHB @ 4 t RHB ha -1 outperforming the other treatments. Phytolith and PhytOC production were found to be significantly correlated to soil organic carbon (OC), available nitrogen (N) and potassium (K), 0.01 M CaCl2 extractable Si (CCSi) and amorphous Si (ASi) content in the soil.Redundancy analysis showed that treatments receiving RHB @ 4 t RHB ha -1 have a stronger relationship with the CCSi and ASi which majorly contributed to the higher phytolith and phytOC PhytOC production. Thus, practicesThus, practices such as Si fertilizers and , in Formatted: Width: 21 cm, Height: 29.7 cm, Numbering: Continuous particular, RHBRHB application have a high potential for phytolith production and PhytOC sequestration, a critical mechanism of the global biogeochemical carbon C sink.